The Effect of Resilience on Productive Work Behavior of Orphanage Caregivers in Tangerang - Natanael Salim; Yusak Novanto (Journal of Educational, Health and Community Psychology, 2022)
Orphanage is one form of non-profit organization. Productive work behavior is needed by orphanage caregivers in carrying out their duties. Productive work behavior is the behavior of a person who contributes positively to both the organization and the environment. One of the factors that influence productive work behavior is resilience. Resilience is the ability to cope with and adapt to severe events or problems that occur in life. This study aims to see whether there is an effect of resilience on productive work behavior in orphanage caregivers in the Tangerang area. The research was conducted quantitatively using the Connor-Davidson Resilience Scale and Productive Behavior measuring instruments. A total of 32 participants from nine orphanages in Tangerang became research subjects using purposive sampling technique.The results prove statistically that resilience affects productive work behavior by 51.9% (R2=.519, B=.728,p=.000;p<.01) uses a simple linear regression technique. The author also found that the dimension of personal competence has the most significant effect on productive work behavior. Suggestions for orphanages in Tangerang to create programs that can increase the resilience of orphanage caregivers and maintain their productive work behavior.